Identification badge lanyards as infection control risk: a cross-sectional observation study with epidemiological analysis. Issue 1 (May 2017) - Murphy, C.M.; Di Ruscio, F.; Lynskey, M.; Collins, J.; McCullough, E.; Cosgrave, R.; McDonnell, D.; Fennell, J.
Summary: Staphylococcus aureus cultures from name badge lanyards were phenotypically and genotypically indistinguishable from the wearer's nasal carrier strains by pulsed-field gel electrophoresis and antibiogram. Lanyards had a mean age of 22 months and hygiene was poor with only 9% ever having been laundered. Molecular analysis showed that 26% of S. aureus nasal carriers shared an indistinguishable strain on their lanyard. Lanyards should not be recommended for staff in frontline clinical care.